Social Determination of the Health of Families from Two Neighborhoods in Medellín, Colombia - Gaviria Noreña, Dora Lucía; Álvarez Del Río, Rusbert Fernando; Zapata Gómez, Nora Eugenia; González Giraldo, Maribel (Investigación y Educación en Enfermería, 2023)
Objective. To understand the health process, from the approach of the social determination of health in two neighborhoods in Medellín - Colombia, to contribute to the care of people, families, and collectives in their multidimensional reality. Methods. Qualitative research from the ethnographic perspective, approaching the general dimension with documentary analysis of social policies and community documents, the particular dimension through focal groups and interviews to community leaders, and the singular dimension with the family visit. Results. Families and collectives live within a sociocultural setting of resistance, overshadowed by moments of flight and displacement derived from violence, with scant participation in city plans and programs and with structural problems of economic and political exclusion. They constructed the territory as space and shelter in the weave that protects and violates them, with processes from uprooting to rooting. The families have maintained protective processes, like family participation in decision making, knowledge on health care, among others, and destructive processes, like informal labor and job instability, without spaces for recreation and with limitations in transportation, in access to health programs and in obtaining food. Conclusion. The health of the families has been determined by historical exclusion to work to obtain resources for a minimum vital subsistence, which is why they suffer social vulnerability due to few opportunities for development; they have lived a transformation process of the territory with resistance, solidarity, and construction of social networks.